Effects of Meditation and Music-Listening on Blood Biomarkers of Cellular Aging and Alzheimer's Disease in Adults with Subjective Cognitive Decline: An Exploratory Randomized Clinical Trial. - Innes, Kim E; Selfe, Terry Kit; Brundage, Kathleen; Montgomery, Caitlin; Wen, Sijin; Kandati, Sahiti; Bowles, Hannah; Khalsa, Dharma Singh; Huysmans, Zenzi (J Alzheimers Dis, 2018)
BACKGROUND: Telomere length (TL), telomerase activity (TA), and plasma amyloid-β (Aβ) levels have emerged as possible predictors of cognitive decline and dementia. OBJECTIVE: To assess the: 1) effects of two 12-week relaxation programs on TL, TA, and Aβ levels in adults with subjective cognitive decline; and 2) relationship of biomarker changes to those in cognitive function, psychosocial status, and quality of life (QOL). METHODS: Participants were randomized to a 12-week Kirtan Kriya meditation (KK) or music listening (ML) program and asked to practice 12 minutes/day. Plasma Aβ(38/40/42) and peripheral blood mononuclear cell TL and TA were measured at baseline and 3 months. Cognition, stress, sleep, mood, and QOL were assessed at baseline, 3 months, and 6 months. RESULTS: Baseline blood samples were available for 53 participants (25 KK, 28 ML). The KK group showed significantly greater increases in Aβ40 than the ML group. TA rose in both groups, although increases were significant only among those with higher practice adherence and lower baseline TA. Changes in both TL and TA varied by their baseline values, with greater increases among participants with values ≤50th percentile (ps-interaction <0.006). Both groups improved in cognitive and psychosocial status (ps ≤0.05), with improvements in stress, mood, and QOL greater in the KK group. Rising Aβ levels were correlated with gains in cognitive function, mood, sleep, and QOL at both 3 and 6 months, associations that were particularly pronounced in the KK group. Increases in TL and TA were also correlated with improvements in certain cognitive and psychosocial measures. CONCLUSION: Practice of simple mind-body therapies may alter plasma Aβ levels, TL, and TA. Biomarker increases were associated with improvements in cognitive function, sleep, mood, and QOL, suggesting potential functional relationships.